1998
DOI: 10.1074/jbc.273.34.21439
|View full text |Cite
|
Sign up to set email alerts
|

The Core Protein of the Chondroitin Sulfate Proteoglycan Phosphacan Is a High-affinity Ligand of Fibroblast Growth Factor-2 and Potentiates Its Mitogenic Activity

Abstract: Using a radioligand binding assay we have demonstrated that phosphacan, a chondroitin sulfate proteoglycan of nervous tissue that also represents the extracellular domain of a receptor-type protein tyrosine phosphatase, shows saturable, reversible, high-affinity binding (K d ϳ6 nM) to fibroblast growth factor-2 (FGF-2). Binding was reduced by only ϳ35% following chondroitinase treatment of the proteoglycan, indicating that the interaction is mediated primarily through the core protein rather than the glycosami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
57
1
3

Year Published

2000
2000
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(65 citation statements)
references
References 19 publications
(18 reference statements)
4
57
1
3
Order By: Relevance
“…The cerebral primordium contains a relatively large number of neural stem cells (1,2), and it is feasible that CSPGs participate in the regulation of their functions as major constituents of their milieu, or the niche. To date, phosphacan has been detected in the neuroepithelium and in the ventricular zone of the fetal rat cerebrum (46,47), but it has been shown that immunoreactivities for aggrecan and versican were very low, if any, in the ventricular zone of the developing rat cerebrum (40). We demonstrated the existence of neurocan, RPTP␤, and NGC in the ventricular zone rich in nestin-positive cells, or neural stem/progenitor cells (Figs.…”
Section: Table 2 Disaccharide Composition Of Hs In Gag Fractions Prepmentioning
confidence: 63%
“…The cerebral primordium contains a relatively large number of neural stem cells (1,2), and it is feasible that CSPGs participate in the regulation of their functions as major constituents of their milieu, or the niche. To date, phosphacan has been detected in the neuroepithelium and in the ventricular zone of the fetal rat cerebrum (46,47), but it has been shown that immunoreactivities for aggrecan and versican were very low, if any, in the ventricular zone of the developing rat cerebrum (40). We demonstrated the existence of neurocan, RPTP␤, and NGC in the ventricular zone rich in nestin-positive cells, or neural stem/progenitor cells (Figs.…”
Section: Table 2 Disaccharide Composition Of Hs In Gag Fractions Prepmentioning
confidence: 63%
“…It mostly consists of hyaluronan, neurocan, versican V0, versican V1, tenascin-C and HAPLN1/Crtl1 (Milev et al 1998b;Rauch 2004). In addition, prominent CNS-expression of aggrecan has been reported in chick embryos (Schwartz and Domowicz 2004), while only very small amounts have been detected in prenatal rodent brains Milev et al 1998c). Cellular origin of neurocan and the large versican variants are neurons (Engel et al 1996;Yamagata and Sanes 2005), whereas aggrecan appears to be mainly expressed by cells of astroglial lineage at this early time point (Domowicz et al 2008).…”
Section: Juvenile Matrix Typementioning
confidence: 99%
“…The core proteins of some proteoglycans (e.g. NG2 and phosphacan) bind to FGF2 (37,38). Direct core protein interactions with signaling components might be lost upon tryptic release of the proteoglycan from the cell surface, explaining the failure of these soluble forms.…”
Section: Fig 8 Fgfr1-activation By Purified Hs Chains and Chain Clumentioning
confidence: 99%